Successful transcutaneous pacing following ventricular standstill during anaesthetic induction in a dog with third‐degree atrioventricular block. Issue 3 (18th August 2020) - Miller, Lucy; Gozalo‐Marcilla, Miguel; Culshaw, Geoff; Panti, Ambra
Abstract : Third‐degree atrioventricular block is a haemodynamically unstable bradycardia frequently resulting in signs of lethargy, weakness and collapse. In this reported case, a four year‐four month‐old male neutered Cavalier King Charles spaniel diagnosed with third‐degree atrioventricular block was referred for transvenous permanent pacemaker implantation. During induction of general anaesthesia, the dog suffered cardiac arrest consistent with ventricular standstill, as indicated by cessation of ventricular electrical activity on the ECG monitor and the absence of a peripheral pulse. The prior placement of transthoracic pacing pads under sedation allowed for rapid commencement of temporary transcutaneous pacing and proved effective in achieving ventricular capture with re‐establishment of cardiac output. The subsequent general anaesthesia for implantation of a permanent pacemaker was uneventful. This report considers the possible causes of ventricular escape rhythm suppression and highlights the importance of ensuring availability of a temporary pacing method from the outset when anaesthetising animals with unstable and symptomatic bradycardias.